Synthesizing and Characterizing Some Pharmaceutical Resins Using Mannich Bases and Studying Their Biological Activity (Baghdad Science Journal, 2024)
Mannich bases functional groups were used, which is considered an inventive phenol formaldehyde resin was created in this study. The project was divided into two phases. The first portion involves creating a monomer of Mannich bases through a condensation reaction. The reaction occurs between aromatic aldehyde (P-hydroxy benzaldehyde) and primary amines like (Metoclopramide, trimethoprim, 2-aminobenzothiazoly, sulfamethoxazole, and 4-amino antipyrine) and with minor amines such as Carbazol. By condensing Mannich bases made in part one with formaldehyde and phenol, the second stage included making phenol formaldehyde resin with Mannich bases. The synthesized resins (Phenol-formaldehyde) have been characterized. The characterization was done by (1H-NMR, and FT-IR)  to determine the degree of biological activity associated with some of the active groups.Keywords: Carbazole, Mannich bases, phenol formaldehyde, polymerization and Resin.